Pelatihan Desain Media Komputasional Interaktif bagi Guru PAUD Desa Cikarang untuk Penguatan Karakter - Yossi Srianita; Dwiyani Anggraeni; Siti Juariah; Nina Amalia Putri (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Early Childhood Education (PAUD) teachers play a crucial role in shaping children's character through creative and meaningful learning processes. However, utilizing digital technology as an interactive learning medium remains a challenge for some PAUD teachers, particularly in rural areas. This community service initiative aims to enhance the competence of PAUD teachers in Cikarang Village regarding the design of interactive computational media that supports character building in early childhood. The implementation method encompasses needs assessment, content delivery, training on media design applications, hands-on media creation, mentoring, and evaluation of training outcomes. PAUD teachers participated actively in every stage of the training. The results demonstrate an improvement in participants' understanding of interactive computational media concepts and their ability to produce engaging, user-friendly learning media that integrate character values such as discipline, responsibility, cooperation, honesty, and caring. This training contributes to enhancing teachers' digital competence while fostering the implementation of learning practices that are more innovative, effective, and child-centered. Consequently, this initiative serves as a strategic effort to support character building through technology-based early childhood education.